COMMUNITY CUSTOM AND FORM OF CHARACTER RESISTANCE IN MEMANG JODOH BY MARAH RUSLI (A STUDY OF IAN WATT'S LITERATURE SOCIOLOGY) - Rahmania Kuku (Jambura Journal of Linguistics and Literature, 2022)
This qualitative descriptive research aimed describe community customs and form of character resistance in "Memang Jodoh" by Marah Rusli as the source of data, with reading and note taking as the data collection technique and steps of classification, analysis, description, and interpretation of data for the data analysis. The data consist of quotes that illustrates the customs and character's resistance on arranged marriage and kinship in "Memang Jodoh" by Marah Rusli. The findings and discussion revealed the customs and resistance on arranged marriage reflects Minangkabau society condition and the writer's vision in changing the society's perspective on the Minangkabau traditions that still upholds classic customs with its values, while Marah Rusli's vision is to correct the social perspective so as to not limit the latitude and burden every person with such rules. Meanwhile, the customs and resistance on kinship reflects the social reality which adopts matrilineal system, in which Marah Rusli's vision on matrilineal system is to repair the social system for it to be maintained. Hence, the community customs and form of character resistance reflects Minangkabau society condition and Marah Rusli's perspective which is expected to adapt to the current situation or age to not limit and burden a person's latitude, especially in making choices. Keywords: Community Customs, Minangkabau, Form of Character Resistance, Novel, Ian Watt Literature Sociology